2015
DOI: 10.1111/bij.12494
|View full text |Cite
|
Sign up to set email alerts
|

Valuing museum specimens: high-throughput DNA sequencing on historical collections of New Guinea crowned pigeons (Goura)

Abstract: Museum specimens are of particular importance for investigating systematics and the biogeography as well as other aspects of the evolution of biodiversity. They are also a depository of specimens accumulated over recent historical times and often the only way to study recently extinct or rare species. Unfortunately, most museum specimens yield low-quality DNA limiting their generalized use in phylogenetic and population genetic studies. Advances in sequencing technologies now offer opportunities to analyse suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 51 publications
(85 reference statements)
1
70
0
Order By: Relevance
“…Although Tsai et al () found no significant difference in quality of DNA between toe‐pads and other sources, they did find that toe‐pads resulted in more DNA than other sources, especially bone. Further, toe‐pads may be preferred because they are usually not subject to treatment with arsenic, which may be present in many older specimens and can affect DNA quality (Besnard et al, ; Topfer et al, ). Skin‐punches : A more rarely used source of genetic material from avian study skins, this method may be particularly useful for specimens with especially delicate feet/legs, or in cases where the feet provide important taxonomic information that would be destroyed by sampling the toe‐pad (Clark, ; Payne & Sorenson, ). This method involves cutting a small piece of skin from the body of the specimen, in one of the apteria, or featherless tracts of skin on a bird.…”
Section: Molecular and Bioinformatic Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Tsai et al () found no significant difference in quality of DNA between toe‐pads and other sources, they did find that toe‐pads resulted in more DNA than other sources, especially bone. Further, toe‐pads may be preferred because they are usually not subject to treatment with arsenic, which may be present in many older specimens and can affect DNA quality (Besnard et al, ; Topfer et al, ). Skin‐punches : A more rarely used source of genetic material from avian study skins, this method may be particularly useful for specimens with especially delicate feet/legs, or in cases where the feet provide important taxonomic information that would be destroyed by sampling the toe‐pad (Clark, ; Payne & Sorenson, ). This method involves cutting a small piece of skin from the body of the specimen, in one of the apteria, or featherless tracts of skin on a bird.…”
Section: Molecular and Bioinformatic Resourcesmentioning
confidence: 99%
“…While this method has the benefit of not showing the damage to the specimen, the quality and quantity of the DNA extracted from this skin tissue may be lower than that sampled from a toe‐pad, given the increased surface area exposed to the environment and the relatively thin layer of tissue. Skin‐punches may also yield lower quality DNA if the specimens were treated with arsenic (Besnard et al, ; Topfer et al, ). In Tsai et al (), skin‐punches generally produced lower yields of DNA, especially when using silica column protocols (see extraction methods below). Feathers : Just as feathers can be plucked from live birds for genetic material, feathers from avian specimens can also be used as a source of DNA.…”
Section: Molecular and Bioinformatic Resourcesmentioning
confidence: 99%
“…; Besnard et al . ). Especially for studies of how species respond to environmental change, habitat loss and changes in population size, the value of museum specimens has increased in recent years (Buerki & Baker ).…”
Section: Introductionmentioning
confidence: 97%
“…Although high‐throughput sequencing has already proved widely useful for incorporating museum specimens into phylogenomic studies (Besnard et al., ; Burbano et al., ; McCormack et al., ), its application for collecting genome‐wide markers at the population level has lagged behind its use for addressing questions at deeper evolutionary time scales due to limitations in the most commonly employed library preparation methods for reduced‐representation Illumina sequencing (Suchan et al., ). The limitations of historic museum samples include their high degree of fragmentation and low concentration of long DNA fragments, which reduces the amount of flanking sequence that can be captured using ultraconserved element probes (Faircloth et al., ) and lowers the likelihood that multiple restriction digest recognition sequences are retained in a given DNA fragment (Baird et al., ; Peterson, Weber, Kay, Fisher, & Hoekstra, ).…”
Section: Introductionmentioning
confidence: 99%